Exercise-induced desaturation during a six-minute walk test is associated with poor clinical outcomes in patients with pulmonary arterial hypertension - Choi, Jung Hyun; Shin, Myung-Jun; Lee, Byeong-Ju; Park, Jae-Hyeong (Clinical hypertension, 2023)
Background The six-minute walk test (6MWT) is an established exercise test for patients with pulmonary arterial hypertension (PAH), affording insight into both exercise intolerance and overall prognosis. Despite the widespread application of the 6MWT, the prognostic implications of exercise-induced desaturation (EID) during this test has been inadequately studied in PAH patients. Thus, we evaluated the occurrence of EID and its prognostic significance in PAH patients. Methods We analyzed PAH patients in a single-center cohort from April 2016 to March 2021. EID was defined as a reduction in oxygen saturation exceeding 4% from the baseline or to below 90% at any point during the test. Results We analyzed 20 PAH patients in this cohort, primarily consisting of 16 females with an average age of 48.4 ± 13.3 years. Among them, ten exhibited EID. Baseline characteristics, echocardiographic data and right heart catheterization data were similar between the two groups. However, total distance (354.3 ± 124.4 m vs. 485.4 ± 41.4 m, P = 0.019) and peak oxygen uptake (12.9 ± 3.2 mL/kg⋅min vs. 16.4 ± 3.6 mL/kg⋅min, P = 0.019) were significantly lower in the EID group. During the total follow-up duration of 51.9 ± 25.7 months, 17 patients had at least one adverse clinical event (2 deaths, 1 lung transplantation, and 13 hospital admissions). The presence of EID was associated with poor clinical outcome (hazard ratio = 6.099, 95% confidence interval = 1.783–20.869, P = 0.004). Conclusions During the 6MWT, EID was observed in a half of PAH patients and emerged as a significant prognostic marker for adverse clinical events. Graphical Abstract